PolSpec: polarisationbased detection for versatile, costeffective rapid hyperspectral imaging - Liu,H; Kumar,S; Garcia,E; Ennis,D; McNeish,IA; French,PMW (Journal of Biophotonics, 2025)
“PolSpec” is a flexible, cost-effective approach for rapid (including single-shot) spectrally resolved imaging. While established approaches, e.g., using cascades of dichroic beamsplitters, diffractive image splitters, or mosaic filters, typically have pre-determined spectral detection bands with cost and experimental complexity scaling with the number of spectral channels, PolSpec uses polarisation optics to provide continuously varying transmission across a configurable spectral range to generate “spectral modulation vectors” that can represent specific spectral signatures with lower data volumes than full spectral profiles. It can be implemented with almost any detector. Here we demonstrate low-cost single-shot widefield PolSpec-based hyperspectral imaging using a polarisation-resolving camera.